Template-directed dye-terminator incorporation (TDI) assay: a homogeneous DNA diagnostic method based on fluorescence resonance energy transfer. - Chen, X (1997)
A new method for DNA diagnostics based on template-directed primer extension and detection by fluorescence resonance energy transfer is described. In this method, amplified genomic DNA fragments containing polymorphic sites are incubated with a 5'-fluorescein-labeled primer (designed to hybridize to the DNA template adjacent to the polymorphic site) in the presence of allelic dye-labeled dideoxyribonucleoside triphosphates and a modified Taq DNA polymerase (Klentaq1-FY). The dye-labeled primer is extended one base by the dye-terminator specific for the allele present on the template. At the end of the genotyping reaction, the fluorescence intensities of the two dyes in the reaction mixture are analyzed directly without separation or purification. This homogeneous DNA diagnostic method, which we call the template-directed dye-terminator incorporation assay, is shown to be highly sensitive and specific and is suitable for automated genotyping of large numbers of samples.